A Thematic Model of Effective Coaching Skills Training for Sports Coaches in Tehran Province: A Qualitative Study - Hoora Heybatzadeh; Mahdi Naderi Nasab; Seyyed Abbas Biniaz (Journal of Foresight and Health Governance, 2026)
Coach education is often treated mainly as technical instruction, although coaches also require communication, leadership, emotional self-regulation, reflective learning, ethical judgment, and contextual awareness. This qualitative study developed a thematic model of effective coaching skills training for sports coaches in Tehran Province. Semi-structured interviews were conducted with 15 participants, including active coaches, sport education and sport management specialists, and academic experts in coach development. Participants were selected through purposive and snowball sampling until data adequacy was judged to have been reached. Data were analysed using a codebook-oriented thematic analysis informed by Braun and Clarke's six-phase procedure. The analysis generated eight themes: specialist and scientific coaching knowledge, communication and interpersonal skills, leadership and team-management competencies, emotional intelligence and self-regulation, experiential learning and reflection, career-path management and professional development, technology and innovative educational approaches, and contextual, cultural, and organizational factors. The model should be interpreted as a conceptual organization of interview-derived themes rather than as a tested causal model. The findings suggest that coach education in this context should move beyond short technical courses and include structured, continuous, reflective, ethically informed, and context-sensitive professional development. Potential implications for athlete-supportive practice and sport governance are discussed cautiously because athlete outcomes and governance effectiveness were not directly measured.